2008
DOI: 10.1080/10615800701628827
|View full text |Cite
|
Sign up to set email alerts
|

Big fish in big ponds: A multilevel analysis of test anxiety and achievement in special gifted classes

Abstract: This study analyzes the effects of individual achievement and achievement level of student reference group on test anxiety in a national sample of 769 gifted Israeli students (grade levels 4Á9), which was previously investigated by Zeidner and Schleyer (1999a). We hypothesized that when controlling for individual achievement, students' experiences of test anxiety should increase with the increasing ability level of their peer reference group. It was assumed that this effect was largely mediated by reference gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(56 citation statements)
references
References 35 publications
4
47
2
Order By: Relevance
“…"Worry" refers to concerns and inner thoughts about failure in respect to self esteem, self focus and self-related thoughts while "emotionality" refers to physiological responses to the test, similar to Liebert & Morris' (1967) concepts of worry and emotionality. It is a well known fact that test anxiety impairs performance and data suggest that both worry and emotionality have negative effects on performance, though worry's are more prominent (Cassady, 2004;Minor & Gold, 1985;Goetz et al, 2008;Lee & Vaughan, 1996;Zeidner, 1998;Zeidner & Matthews, 2005).…”
Section: Test Anxietymentioning
confidence: 99%
“…"Worry" refers to concerns and inner thoughts about failure in respect to self esteem, self focus and self-related thoughts while "emotionality" refers to physiological responses to the test, similar to Liebert & Morris' (1967) concepts of worry and emotionality. It is a well known fact that test anxiety impairs performance and data suggest that both worry and emotionality have negative effects on performance, though worry's are more prominent (Cassady, 2004;Minor & Gold, 1985;Goetz et al, 2008;Lee & Vaughan, 1996;Zeidner, 1998;Zeidner & Matthews, 2005).…”
Section: Test Anxietymentioning
confidence: 99%
“…When gifted students are in programs with only other gifted students, comparisons with their peers may shift, such that the student is no longer the highest achiever in his or her class. In gifted-centered classes or programs, gifted students may even have a heightened awareness of the achievement of their peers and how it compares with their own (Wang, Fu, & Rice, 2012), and these students tend to exhibit higher levels of anxiety reasons for anxieity in this population: competition with other gifted students, real or perceived pressures for success or achievement placed upon them by others (Aljughaiman & Tan, 2008;Goetz et. al., 2008;Zeidner & Schleyer, 1999).…”
Section: Other Academic Anxietymentioning
confidence: 99%
“…Skill building can include teaching study or test-taking skills (Goetz et al, 2008). Counselors and other professionals working with gifted youth in educational settings accidently overlook the need for these skills in gifted youth when a student has displayed a pattern of high achievement.…”
Section: Perfectionism and Academic Anxietymentioning
confidence: 99%
See 1 more Smart Citation
“…Test anxiety, which is a type of anxiety, is the consequence of the debilitative aspects of anxiety and shows itself when one is getting ready for an exam or is in the process of taking it (Onyeizughbo, 2010) Ziedner (1998 cited in Chamorro, Permuzic, Ahmetoglu & Furnham, 2008) defines test anxiety as a set of phenomenological, physiological and behavioral responses that accompany concern about possible negative consequences or failure on an exam or similar evaluative situation. There are many researches, both in the laboratory settings and environments such as universities and schools have shown that test anxiety hinders people's academic progress (Goetz, Preckel, Zeidner, & Schleyer, 2008). Moreover, Du introduces a type of anxiety and calls it language anxiety.…”
Section: Introductionmentioning
confidence: 99%